QUALITATIVE ANALYSIS OF AROMATIC OXIDE COMPOUNDS - Khalikova Gulhayo Koldoshevna; Rakhimov Firuz Fazlidinovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article presents a qualitative analysis of benzene-based oxycompounds. The most suitable option of qualitative analysis is selected. Also, a modern physico-chemical research method - infrared spectroscopic analysis - is presented for qualitatively distinguishing benzene series oxycompounds from each other, and the characteristic absorption spectra were determined as a result of spectral analysis.